СРАВНЕНИЕ ДВОЙНОГО Z-ИНВЕРТОРА С КЛАССИЧЕСКИМ ИНВЕРТОРОМ ДЛЯ СИСТЕМЫ ЭЛЕКТРОСНАБЖЕНИЯ САМОЛЕТА - Хлебников, А.С.; Бачурин, П.А.; Гейст, А.В.; Решетников, А.Н.; Балагуров, М.В. (Інститут електродинаміки НАН України, Київ, 2012)
The scheme of the dual Z-Source inverter with the raised quality of formed voltages is proposed. Results of modeling of the converter as a part of aviation system of generating of electric energy are presented; comparison of this scheme with the scheme of the classical voltage source inverter is made. Work is executed under the state contract ???? 13.G36.31.0010 from 22.10.2010. References 4, figures 3.